Carbon based-materials/metal-organic framework for catalytic oxidation in direct borohydride fuel cell application - Nik Farah Hanis Nik Zaiman; Norazuwana Shaari; Zatil Amali Che Ramli (Penerbit Universiti Kebangsaan Malaysia, 2023)
Metal-organic frameworks (MOFs), are known as novel types of crystalline materials formed by organic bridging ligands and coordination of metal ions. MOFs have unique characteristics such as high porosity, large surface area, and high structural durability. However, MOFs have some disadvantages such as having low stability, as well as electrical conductivity which causes their catalysis efficiency and application to be limited to a large extent. Thus, among the solutions made in previous studies, to overcome the disadvantages of this MOF is to combine it with carbon-based material to form a composite with better properties than pure MOF. This current review focuses on the performance of carbon-based material/MOF catalyst composites for direct borohydride fuel cell (DBFC) application. The catalytic oxidation of borohydride performance using carbon-based material/MOF catalyst is clearly and scientifically observed to enhance the catalytic activity in previous studies. There is no denying that carbon-based materials are widely used in fuel cell applications and have great advantages such as low toxicity, unique structure, good porosity properties, lightweight, controllable heteroatom doping, and easy processing, as well as excellent mechanical, chemical, and thermal properties. Thus, this review provides a summary of the application of carbon-based materials and MOFs with the properties and performance of this composite including the catalytic oxidation activity and DBFC potential for the entire system.